Elliptic Curve Cryptography based Security on MQTT System for Smart Home Application - Yusoff, Z.Y.M. (Institute of Electrical and Electronics Engineers Inc., 2022)
Securing IoT networks has been one of recent most active research topics. However, unlike traditional network security, where the emphasis is given on the core network, IoT networks are mostly investigated from the data stand-point. Lightweight data transmission protocols, such as Message Queue Telemetry Transport (MQTT), are often deployed for data-sharing and device authentication due to limited onboard resources. This paper presents the MQTT protocol's security vulnerabilities by incorporating Elliptic Curve Cryptography-based (ECC-based) security to improve confidentiality issues. We used commercially off-the-shelf (COTS) devices such as Raspberry Pi to build a simplified network topology that connects IoT devices in our smart home laboratory. The results illustrate an ECC-based security application in confidentiality increase of 70.65 from 29.35 in time parameter during publish/subscribe communication protocol for the smart home. Â© 2022 IEEE.